Pythagorean Calc Aplication: Is It Effective in Mathematical Understanding Ability? - Lestari, Puji; Ruhma, Salwa Zakiyah (Mathematics Education Journal, 2024)
Understanding mathematics requires deep thinking to learn it meaningfully. However, empirically, many students face complex difficulties in understanding mathematical concepts. This study aimed to determine the quality of improvement before and after using the Pythagorean Calculator application and to find out the effectiveness of using the Calc application on the student's ability to understand mathematics. This research uses a quantitative approach with a quasi-experimental method. This study was conducted at one of the private MTs in Ciamis district, West Java, by taking samples using purposive sampling, namely Class VIII B in the 2023/2024 academic year with a total of 21 students. Data was collected through a high-level mathematical understanding ability test based on the Polya indicator. The results of the research show that the quality of improvement in mathematical understanding abilities after learning assisted by the Pythagorean Calc application on the Pythagorean theorem material with the level of difference is in the medium category. Using the Pythagorean Calc application is effective in improving mathematical understanding abilities and is classified as a strong effect category.